(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Employee performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Lack of communication and collaboration between employees and employees with leaders. The purpose of this study was to determine the effect of human relations, organizational commitment, and work discipline on employee performance. The sample of this research was civil servants at UPTD Puskesmas Manggis I, totaling 51 people. Samples were taken using purposive sampling method. The research method used is multiple linear regression analysis. The data analysis technique used is validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the research results it can be seen that: (1) The human relations variable has proven to have a positive and significant effect on the performance of civil servants . (2) Organizational commitment variable is proven to have a positive and significant effect on the performance of civil servants. (3) The work discipline variable has also proven to have a positive and significant effect on the performance of civil servants. (4) Human relations, Organizational Commitment and Work Discipline simultaneously have a positive and significant effect on employee performance. The magnitude of the variation in influence between Human relations, Organizational Commitment and Work Discipline on employee performance is 81.1%